2015
DOI: 10.5152/iao.2015.1227
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Idiopathic Sudden Sensorineural Hearing Loss

Abstract: OBJECTIVE:The objective was to identify and evaluate factors that may influence the recovery rate in patients with idiopathic sudden sensorineural hearing loss (ISSNHL). MATERIALS and METHODS:A retrospective analysis was performed for patients with sudden sensorineural hearing loss between 2009 and 2013. Those with an identified etiology were excluded. The patients were divided into four treatment groups: (i) systemic corticosteroids (SC) only, (ii) SC+low-molecular-weight heparin (LMWH), (iii) SC+hyperbaric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
4
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 30 publications
3
50
4
4
Order By: Relevance
“…In a similar regression analysis for patients receiving combined oral1IT having greater than 30 dB improvement in PTA, age was not statistically correlated with outcomes. 8 In earlier literature, older age in treated ISSNHL patients tends to be associated with a worse prognosis [12][13][14][15] or no change in hearing improvement. [16][17][18] One prospective, longitudinal cohort study of 127 ISSNHL patients found no significant difference in PTA recovery rates in the various age groups studied (30, 31-50, 51-70, 71 years old), but did note a trend in poorer results in the more extreme age groups (30, 71 years old) 19 Attanasio et al 20 found increased age was associated with worse hearing outcomes in their study of 496 patients; on subgroup analysis divided by age >65 years old, patients in the older subgroup had a statistically significant higher PTA both pre-and posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar regression analysis for patients receiving combined oral1IT having greater than 30 dB improvement in PTA, age was not statistically correlated with outcomes. 8 In earlier literature, older age in treated ISSNHL patients tends to be associated with a worse prognosis [12][13][14][15] or no change in hearing improvement. [16][17][18] One prospective, longitudinal cohort study of 127 ISSNHL patients found no significant difference in PTA recovery rates in the various age groups studied (30, 31-50, 51-70, 71 years old), but did note a trend in poorer results in the more extreme age groups (30, 71 years old) 19 Attanasio et al 20 found increased age was associated with worse hearing outcomes in their study of 496 patients; on subgroup analysis divided by age >65 years old, patients in the older subgroup had a statistically significant higher PTA both pre-and posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…In ISSHL, patients reported higher stress levels and more stressful life-events before the sudden hearing loss occurred when comparied with healthy controls. While certain single-case studies have reported the association between stress and ISSHL which used qualitative interviews as assessment instruments (14)(15)(16) . However, any standardized assesment methods were not found, and quantitative statistical analysis of the collected data was not performed Two other studies, which limited by method and design, had similar results (14,16) .…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with ISSNHL improve in hearing within 1 month after the beginning of hearing loss, but some patients improve within 4 months 4. Around 32%–65% of patients with ISSNHL may spontaneously recover their hearing,5 but treatment is still suggested because of the uncertainty of the outcome and the effects of hearing impairment on the quality of life. The aim in ISSNHL treatment is to decrease the inflammatory response and increase the blood supply and oxygen saturation 5.…”
Section: Discussionmentioning
confidence: 99%
“…Around 32%–65% of patients with ISSNHL may spontaneously recover their hearing,5 but treatment is still suggested because of the uncertainty of the outcome and the effects of hearing impairment on the quality of life. The aim in ISSNHL treatment is to decrease the inflammatory response and increase the blood supply and oxygen saturation 5. Despite there were being many possible treatment policies in current clinical practice nowadays, there is a lack of consensus about the definitive treatment for ISSNHL.…”
Section: Discussionmentioning
confidence: 99%